2017
DOI: 10.1016/j.eats.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Capsular Fixation: An Implant-Free Technique to Prevent Meniscal Allograft Extrusion

Abstract: Although several surgical techniques have been described to perform meniscal allograft transplantation with good clinical results and although different methods of capsular stabilization can be found in the literature, there is no standard surgical technique to prevent a common complication in the most of series: the tendency to a radial displacement or extrusion of the transplanted menisci. We present a simple, reproducible, and implant-free technique to perform a lateral capsular fixation (capsulodesis) at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Both techniques have been previously described in detail 6,10 . The recipient bed preparation was similar in all cases.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Both techniques have been previously described in detail 6,10 . The recipient bed preparation was similar in all cases.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The whole surgical technique was performed arthroscopically in all the cases. The specific details of the suture-only [10,14] as well as the capsulodesis techniques have been previously described [12,15]. In all the procedures, the remains of the host menisci were assessed and refreshed using a combination of shaving, rasping and high frequency trephination to promote healing [16].…”
Section: Surgical Techniquementioning
confidence: 99%
“…Intended to address several factors related to extrusion, they are the anatomical implantation of the graft,70 the excision of peripheral osteophytes of the tibial plateau71 and the fixation of the meniscus allograft on the tibial surface 72. More recently, the reduction and fixation of the lateral capsule to the tibia has been put forth 73. Interestingly, based on the available evidence, extrusion seems to produce no adverse outcomes, either clinical or radiological.…”
Section: Allograft Extrusionmentioning
confidence: 99%
“…Currently, three areas of research are identified: (1) optimisation of meniscus allograft transplantation with focus on graft biology and graft extrusion; efforts to minimise extrusion by additional fixation of the graft to the bone, additional fixation of the meniscus ‘skirt’ to the tibial plateau and ‘belt’-type approaches to prevent the capsule to extrude are under current investigation73; (2) better understanding of the patient-specific healing potential by diagnosing good and bad healers prior to surgery; (3) design of scaffolds and implants to substitute meniscus tissue.…”
Section: Specific Populationmentioning
confidence: 99%